Perbedaan Efektivitas Ekstrak Jahe Dengan Ekstrak Kunyit Dalam Mengurangi Nyeri Dismenorhea Primer Pada Mahasiswi Di Asrama Jurusan Kebidanan Poltekkes Surakarta - Gita Kostania; Anik Kurniawati (Interest : Jurnal Ilmu Kesehatan, 2016)
Abstract: Dysmenorrhoea, Ginger, Turmeric. The aim of this study was to determine differences in the effectiveness of ginger extract with turmeric extract on reducing pain in primary dysmenorrhoea on dormitory student at the Midwifery Department of Health Polytechnic of Surakarta. The design of this research is experimental design, with a truly experimental approach, using a pretest-post test control group design. Criteria sampling is purposive random sampling, a total sample of 60 respondents (55% of the population, nomogram Harry King Samples), divided into three equal groups: ginger extract treatment group, turmeric extract treatment group, and placebo group. Each group consists of 20 respondents. Results: the data was in a normal distribution, the total number of respondents at the end of the study was 56 respondents (ginger extract treatment=19, turmeric extract treatment= 19, and placebo=18). There are differences in the effectiveness of ginger extract with turmeric extract in reducing pain in primary dysmenorrhoea on dormitory student at the Midwifery Department of Health Polytechnic of Surakarta (p-value=0.04 <0.05). Extracts of ginger are more effective in reducing menstrual pain than turmeric extract (t-test = 9.690> 4.802).